Embodying Space through Improvisation in Site-Specific Dance Performance - Abdul Wahid, Nurulakmal; Michael, Nur Nabila; Saearani, Muhammad Fazli Taib; Ahmad, Muhammad Faisal (Universitas Negeri Semarang, 2025)
Site-specific dance choreography develops as a direct reaction to a specific location’s unique physical, architectural, and cultural characteristics. Improvisation is significant in this context for enhancing the dancer’s bodily awareness of space. Previous studies have recognized the relationship between dancer and site; however, the role of improvisation in expressing the unique spatial characteristics of a performance site has not been adequately explored. This study investigates the role of improvisational techniques in enabling dancers to adapt, respond, and establish stronger connections with site-specific elements, including structural, environmental, historical, and emotional aspects. This research utilizes a qualitative methodology, incorporating descriptive analysis and in-depth interviews with five experienced, site-specific dance practitioners in Malaysia. The findings identify four key stages in which improvisation enhances spatial embodiment, clarifying the relationship between choreographers and performers with space as a dynamic and interactive element of their practice. This work contributes to the ongoing discussion on site-specific choreography by illustrating the evolving role of improvisation in enhancing the relationships between performers and their environments.